Prediction of preoperative intrathoracic adhesions for ipsilateral reoperations: sliding lung sign - Gaetana Messina; Mary Bove; Antonio Noro; Giorgia Opromolla; Giovanni Natale; Francesco Leone; Vincenzo Di Filippo; Beatrice Leonardi; Mario Martone; Mario Pirozzi; Marianna Caterino; Sergio Facchini; et al. (Journal of Cardiothoracic Surgery, 2022)
Abstract Introduction Video-assisted thoracic surgery (VATS) for ipsilateral reoperations is controversial, because after the first surgical intervention, pleural adhesions occur frequently in the thoracic cavity and/or chest wall. This study assessed the usefulness of preoperative ultrasonography to reduce the incidence of lung injury at the time of the initial port insertion during secondary ipsilateral VATS. Materials and methods This was a retrospective, single-center study. Nine patients who underwent thoracic surgery at Vanvitelli Hospitalfrom September 2019 to February 2022, were scheduled for a second VATS surgeryon ipsilateral lung, because of inconclusive intraoperative histologic examination. All nine patients underwent preoperative ultrasonography to assess the possible presence of pleural adhesions. We evaluated the lung sliding, since the presence of pleural adhesions does not permit to appreciate it. Statistical analysis Hard severe adhesions were observed in all nine patients without sliding lung sign (specificity 100%). In this series, the sensitivity, PPV, and NPV of the sliding lung sign were 93%, 100% and 94% respectively. Results The presence of the lung respiratory changes can be evaluated as the “sliding lung sign” by chest ultrasonography; we believe that the sliding lung sign might also predict intrathoracic adhesion. Conclusions Preoperative detection of pleural adhesions using transthoracic ultrasonography was useful for ipsilateral secondary pulmonary resection patients undergoing VATS. Using preoperative ultrasonography can improve the safety and feasibility of placing the initial port in VATS.